Priority interventions to improve maternal and child diets in Sub-Saharan Africa and South Asia - Masters, William A.; Rosettie, Katherine L.; Kranz, Sarah; Pedersen, Sarah H.; Webb, Patrick; Danaei, Goodarz; Mozaffarian, Dariush; Covic, Namukolo; Mavrotas, George (Wiley, 2018)
Nutrition-sensitive interventions to improve overall diet quality are increasingly needed to improve maternal and child health. This study demonstrates feasibility of a structured process to leverage local expertise in formulating programmes tailored for current circumstances in South Asia and Africa. We assembled 41 stakeholders in 2 regional workshops and followed a prespecified protocol to elicit programme designs listing the human and other resources required, the intervention's mechanism for impact on diets, target foods and nutrients, target populations, and contact information for partners needed to implement the desired programme. Via this protocol, participants described 48 distinct interventions, which we then compared against international recommendations and global goals. Local stakeholders' priorities focused on postharvest food systems to improve access to nutrient-dense products (75% of the 48 programmes) and on production of animal sourced foods (58%), as well as education and social marketing (23%) and direct transfers to meet food needs (12.5%). Each programme included an average of 3.2 distinct elements aligned with those recommended by United Nations system agencies in the Framework for Action produced by the Second International Conference on Nutrition in 2014 and the Compendium of Actions for Nutrition developed for the Renewed Efforts Against Child Hunger initiative in 2016. Our results demonstrate that a participatory process can help local experts identify their own priorities for future investments, as a first step in a novel process of rigorous, transparent, and independent priority setting to improve diets among those at greatest risk of undernutrition.